Recursos terapêuticos utilizados por fisioterapeutas brasileiros no alívio da dor do trabalho de parto - Gonçalves, Alessandra de Campos (2021)
The parturition process is defined as an approach to labor and birth that maximizes the inherent strength and physiology of the woman and fetus, refraining from interventions unless the well-being or safety of both is at risk. There is recognition that pain in labor needs to be relieved, as it can negatively impact both the mother and the fetus. To alleviate pain during the parturition process, pharmacological and non-pharmacological resources are available. We sought to identify the therapies and non-pharmacological resources used by Brazilian physiotherapists to relieve the pain of women in the parturition process. This is a cross-sectional study, using an online questionnaire. Data on the characteristics of study participants and information on the choice of using interventions for pain relief in parturients were collected through an online questionnaire. A descriptive analysis was performed using frequency values (absolute and relative). An association test was also performed between sociodemographic variables and therapies and non-pharmacological resources used for pain relief during the parturition process. One hundred and fourteen physiotherapists working in the field of Obstetrics participated in the study. Among the therapies and resources covered in the questionnaire, it is interesting to note that device-assisted kinesiotherapy was selected by all participants. In addition, we also observed that specialists in Physiotherapy in Women's Health through the CERTAME (COFITO/ABRAFISM) recommend aromatherapy less than professionals without this title (p = 0.008). Brazilian physiotherapists choose to use non-pharmacological therapies and resources for pain relief during labor and delivery that are within the scope of the physiotherapist's practice Kinesiotherapy with the aid of devices is the most used by physical therapists to relieve pain during the parturition process.